Pengembangan Produk Anyaman Mansiang di Palupuh, Kabupaten Agam - Agustia, Naldi (TSAQOFAH, 2025)
This study aims to identify and describe the dyeing process of mansiang weaving materials in Palupuh, Agam Regency. A qualitative approach was employed using the 4D product development model (Define, Design, Develop, Disseminate), with local artisans and community leaders serving as the primary informants. The research instrument consisted of interview guides formulated based on the issues under study, while data collection techniques included in-depth interviews and documentation. The findings indicate that the dyeing process of mansiang follows traditional stages involving the use of simple tools and synthetic dyes. The steps include: (1) preparing a pot filled with water, (2) heating the water to a boil, (3) adding dye to the boiling water, (4) stirring the dye solution until evenly mixed, (5) inserting mansiang stalks into the solution, (6) stirring the mansiang to ensure even color absorption, and (7) removing and drying the dyed mansiang. These findings contribute to the preservation of local knowledge and provide a foundation for developing culturally-based woven craft products that are more innovative and economically valuable.